Comparison of microbial communities and the profile of sulfate-reducing bacteria in patients with ulcerative colitis and their association with bowel diseases: a pilot study - Kushkevych, Ivan; Martínková, Kristýna; Mráková, Lenka; Giudici, Francesco; Baldi, Simone; Novak, David; Gajdács, Márió; Vítězová, Monika; Dordevic, Dani; Amedei, Amedeo; Rittmann, Simon K-M R (Microbial cell (Graz, Austria), 2024)
Considerable evidence has accumulated regarding the molecular relationship between gut microbiota (GM) composition and the onset (clinical presentation and prognosis of ulcerative colitis (UC)). In addition, it is well documented that short-chain fatty acid (SCFA)-producing bacteria may play a fundamental role in maintaining an anti-inflammatory intestinal homeostasis, but sulfate- and sulfite reducing bacteria may be responsible for the production of toxic metabolites, such as hydrogen sulfide and acetate. Hence, the present study aimed to assess the GM composition - focusing on sulfate-reducing bacteria (SRB) - in patients with severe, severe-active and moderate UC. Each one of the six enrolled patients provided two stool samples in the following way: one sample was cultivated in a modified SRB-medium before 16S rRNA sequencing and the other was not cultivated. Comparative phylogenetic analysis was conducted on each sample. Percentage of detected gut microbial genera showed considerable variation based on the patients' disease severity and cultivation in the SRB medium. In detail, samples without cultivation from patients with moderate UC showed a high abundance of the genera Bacteroides, Bifidobacterium and Ruminococcus, but after SRB cultivation, the dominant genera were Bacteroides, Klebsiella and Bilophila. On the other hand, before SRB cultivation, the main represented genera in patients with severe UC were Escherichia-Shigella, Proteus, Methanothermobacter and Methanobacterium. However, after incubation in the SRB medium Bacteroides, Proteus, Alistipes and Lachnoclostridium were predominant. Information regarding GM compositional changes in UC patients may aid the development of novel therapeutic strategies (e.g., probiotic preparations containing specific bacterial strains) to counteract the mechanisms of virulence of harmful bacteria and the subsequent inflammatory response that is closely related to the pathogenesis of inflammatory bowel diseases.
Keywords: 16S rRNA gene sequencing; gut dysbiosis; inflammatory bowel disease; ulcerative colitis; sulfate-reducing bacteria; gut microbiota